SEGMENTATION OF CROSS-CHANNELS IN THE CONDITIONS OF DEVELOPMENT OF THE INFORMATION SYSTEM OF THE CREDIT AND FINANCIAL SECTOR - S. Galazova; L. Magomaeva (Вестник университета)
The development of a new cross-channel information system of the credit and financial sector requires the introduction of new technologies and tools, which ultimately necessitates the use of segmentation methods. Cross-channel segmentation is considered to be the most sensitive part of the development strategy of the information system in the credit and financial sector, as it determines the target segments and their impact on the development strategy of the entire financial market. The fundamentals of building an information cross-channel of the credit and financial sector are identified, the observed and unobservable features of customers are identified, adapted to the needs of specific products and services of the financial market.